Electrocardiographic Study in Adult Homozygous Sickle Cell Disease Patients in Lagos, Nigeria. (21st September 2016) - Dosunmu, Adedoyin; Akinbami, Akinsegun; Uche, Ebele; Adediran, Adewumi; John-Olabode, Sarah
Abstract : Background . This study sought to identify the pattern of electrocardiographic changes in steady state adult sickle cell anaemia. Methods. A case-control, cross-sectional study was conducted amongst sickle cell patients attending the sickle cell clinic of Lagos State University Teaching Hospital, Ikeja, and HbAA controls. All consenting participants had haemoglobin electrophoresis done and were subjected to electrocardiography (ECG). The descriptive data were given as means ± standard deviation (SD). The differences were considered to be statistically significant when the p value obtained was <0.05. Results. A total of ninety-three sickle cell anaemia (SCA) patients and ninety haemoglobin AA (controls) were enrolled. There was no significant difference in the age of the participants with SCA and that of the controls but the body mass index was significantly higher in controls (p = 0.0001 ). Overall, 73.1% (68 of 93) had abnormal ECG while only 2 of 90 (2.2%) of controls had abnormal ECG. The common abnormalities observed were left ventricular hypertrophy, biventricular hypertrophy, and right ventricular hypertrophy. Conclusion. Patients with SCA in steady state tend to have normal heart rate but about 50% of them would have had ECG changes before the age of 20 years. ECG being a noninvasive test may be used to identify patients at risk for early intervention.